Association between depression and the lack of adherence to antituberculosis treatment - Llanos-Tejada, Félix (2019)
Objective: To determine the association between depression and the lack of adherence to antituberculosis treatment in patients treated at the National Hospital Dos de Mayo (Lima, Perú) in 2017. Material and Methods: Observational, descriptive and prospective study carried out in 50 TB patients who completed the first phase of the Sensitive treatment scheme. PHQ-9 questionnaire was applied to determine depression, and Morisky-Green questionnaire to evaluate adherence to treatment. Results: 28 male and 22 female patients with normal nutritional status, recently diagnosed with pulmonary TB were assessed. Average number of fouls was 6.5. 38% of patients were non-adherent, and depression was present in 76%., according to the instruments used. (p> 0.05). There was also a statistically significant association between adherence and having 5 or more faults during the 1st Phase. Conclusions: There is an association between adherence to anti-TB treatment and depression. Similarly, high frequency of non-adherence to treatment in the first phase and high frequency of symptoms suggestive of depression, and association between adherence and having 5 or more faults.